2017
DOI: 10.1126/science.aan2506
|View full text |Cite
|
Sign up to set email alerts
|

Changing climate shifts timing of European floods

Abstract: A warming climate is expected to have an impact on the magnitude and timing of river floods; however, no consistent large-scale climate change signal in observed flood magnitudes has been identified so far. We analyzed the timing of river floods in Europe over the past five decades, using a pan-European database from 4262 observational hydrometric stations, and found clear patterns of change in flood timing. Warmer temperatures have led to earlier spring snowmelt floods throughout northeastern Europe; delayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
635
2
10

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 729 publications
(685 citation statements)
references
References 27 publications
38
635
2
10
Order By: Relevance
“…Additionally, it can be difficult to disentangle the effects of changing climate, land cover, channel morphology, and human activities (2,4). On page n of this issue, Blöschl et al (5) overcome these problems through a consistent pan-European assessment of observed flood seasonality trends between 1960 and 2010. They thus provide the first evaluation of how climatic changes are influencing flood regimes at the continental scale.…”
Section: Measuring the Changing Pulse Of Riversmentioning
confidence: 99%
“…Additionally, it can be difficult to disentangle the effects of changing climate, land cover, channel morphology, and human activities (2,4). On page n of this issue, Blöschl et al (5) overcome these problems through a consistent pan-European assessment of observed flood seasonality trends between 1960 and 2010. They thus provide the first evaluation of how climatic changes are influencing flood regimes at the continental scale.…”
Section: Measuring the Changing Pulse Of Riversmentioning
confidence: 99%
“…Kumar et al, 2009;Milly et al, 2005;Small et al, 2006;Stahl et al, 2010Stahl et al, , 2012, indices that can be used to characterize changes in the seasonal cycle (e.g. Blöschl et al, 2017;Cunderlik and Ouarda, 2009;Ehsanzadeh and Adamowski, 2010;Hidalgo et al, 2009;Moore et al, 2007;Rauscher et al, 2008;Regonda et al, 2005;Stewart et al, 2005), time series of annual percentiles (e.g. Lins and Slack, 1999;Zhang et al, 2001), flood indices (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The inevitable trend of global climate change has brought about considerably frequent occurrences of extreme climate events [1][2][3][4]. Recently, under the influence of typhoons, urban floods caused by rainstorms have exerted great harm on the safety of society.…”
Section: Introductionmentioning
confidence: 99%